Inspection of the Level of Effects of Service Quality to Customer Satisfaction in Retail Supermarkets - Nguyen Thi Hang; Pham Minh Dat; Nguyen Van Huan; Truong Thi Viet Phuong (SIASAT, 2020)
For every business dealing in goods and services, especially in the field of sales, attracting more and more buyers will help increase sales, contributing to achieving the ultimate goal of the producer. Profit maximization. Currently, retail supermarkets are facing fierce competition pressure among supermarket organizations: from the competition of existing supermarkets in the area, the chains of buffet goods, the shopping centers, the penetration of the "giants" in the domestic and foreign retail supermarket industry. In the context of consumers having more and more opportunities to choose shopping places and more and more requirements for service quality, especially, consumers when they come to supermarkets are not merely Buy the goods you need but also feel comfortable, feel your needs are best met. Therefore, when it comes to customer satisfaction with supermarkets, the issues that we need to pay attention to, from the quality of goods to the attitude of the staff, the promotions, as well as pay attention to customers' feelings about the service quality of the business, thereby taking measures to keep old customers, attract new customers ... All have certain effects on customer satisfaction in Supermarkets in general and at retail supermarkets in particular. This study uses exploratory factor analysis (EFA) and positive factor analysis (CFA) to test the scale of the influence of factors on customer satisfaction at the supermarket. The study has determined the scale of affecting factors including 7 components with 27 observed variables. The results of the study help to verify the qualitative statements about the impact of factors on customer satisfaction, thereby drawing conclusions and recommendations to help supermarkets promote points. Strong as well as improve weak points to achieve the best service quality.